Women, Marriage and Migration in the Bangladeshi Enclaves in the India–Bangladesh Borderland. (March 2023) - Roy, Anamika
Based on an ethnographic study of former Bangladeshi enclaves in India, the article explores how the India–Bangladesh border is negotiated and reproduced in the everyday spaces of people living in the borderland that is often overlooked by the usual representation of geopolitical nationalism and hard realities of the barbed wire. Enclaves are fragmented territories surrounded by another state, such as Bangladeshi enclaves surrounded by Indian land and vice versa. Being abandoned by the home state, the former enclave residents were deprived of identity documents, and as a result, precluded from judicial and citizenship rights. The article focuses on marriage-related migration of women that was often used as a way out to overcome the vulnerabilities associated with living in the enclaves. Marriage proposal inside the host country promises access to public goods like a 'Ration Card', or identity documents like an 'Aadhaar card', thus determining the possible migration of women—their life paths and destinations across the enclaves and the host country. The latitudes of such migratory life courses of women along the border are determined by their religion and economic status. The study shows that these practices, although often necessary for survival, subsequently compromise the agency of the women in the process.